(untitled) (Mediscope, 2015)
The aim of the observational case control study was to find out the association of type 2 diabetes mellitus (T2DM) with serum adiponectin level in Bangladeshi population. This was conducted in the Biomedical Research Group, Research Division, Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM), Dhaka, Bangladesh. Sixty six T2DM subjects and seventy four healthy control subjects were included. Diabetes was diagnosed and classified as per World Health Organization criteria. Serum adiponectin was measured by Enzyme Linked Immunosorbent Assay (ELISA) method. Serum glucose was measured by glucose-oxidase method; serum insulin was measured by chemiluminescence- based ELISA technique. The insulin secretory capacity (HOMA%B), insulin sensitivity (HOMA%S) & insulin resistance (HOMA-IR) were assayed by homeostasis model assessment method. Statistical analysis was performed using SPSS Windows version 11.5. The median (range) fasting serum insulin of control and T2DM subjects were 14.7 (1.9-45.9) and 18.1 (4.1-42.8), respectively. The median (range) serum adiponectin (?g/ml) of the control and T2DM subjects were 8.7 (0.8-16.0) and 6.2 (1.1-22.4). The serum adiponectin of T2DM was significantly lower than the control subjects (p < 0.001). The median (range) HOMA%B values of control and T2DM subjects were 160.1 (33.4-493.4) and 100.5 (17.7-349.3), respectively. The median HOMA%B of T2DM subjects was significantly lower than the control subjects (p < 0.001). The median (range) HOMA%S values of control and T2DM subjects were 44.2 (9.8-339.4) and 32.8 (14.3-154.7), respectively. The median HOMA%S of T2DM group was significantly lower than the control subjects (p < 0.05). The median (range) HOMA-IR of control and T2DM subjects were 3.5 (0.5-11.4) and 5.8 (1.0-28.3), respectively. The median HOMA-IR of T2DM subjects was significantly higher than the control subjects (p < 0.001). The results of the study suggest that T2DM subjects have both insulin secretory defects, insulin resistance and associated with lower serum adiponectin level in Bangladeshi population. Mediscope Vol. 2, No. 2: July 2015, Pages 16-21